CHYR1 ubiquitinates the phosphorylated WRKY70 for degradation to balance immunity in Arabidopsis thaliana. Issue 3 (16th February 2021) - Liu, Huanhuan; Liu, Bao; Lou, Shangling; Bi, Hao; Tang, Hu; Tong, Shaofei; Song, Yan; Chen, Ningning; Zhang, Han; Jiang, Yuanzhong; Liu, Jianquan
Summary: It is critically important for plants to control the trade‐off between normal growth and pathogen immunity. However, the underlying molecular mechanism remains largely unknown. Here we report such a mechanism controlled by WRKY70 and its partner CHYR1 in Arabidopsis. We found that both levels of the WRKY70 target gene SARD1 and the phosphorylated forms of WRKY70 were increased in WRKY70OE plants upon Pst DC3000 infection. Mechanistically, phosphorylation of WRKY70 at Thr22 and Ser34 occurs, which then activates SARD1 expression through binding to a WT box. Phosphorylated WRKY70 is degraded by 26S proteasome via CHYR1 when resuming normal growth after infection. In addition, nonphosphorylated WRKY70 represses SARD1 expression by binding to both W (inhibitory activity site) and WT (active activity site) boxes. The binding of WRKY70 to alternative cis ‐elements of SARD1 through a phosphorylation‐mediated switch controlled by CHYR1 contributes to modulating the balance between immunity and growth.